Visualisasi Nilai Spiritual Dewa Ruci dalam Karya Seni Lukis - Iman Budiman; Ariesa Pandanwangi; Belinda Sukapura Dewi (Ideas Publishing, 2023)
The puppet play Dewa Ruci contains many values, including spiritual values. This research aims to discuss the spiritual values of the play as expressed in a two-dimensional work. The works discussed in this research were created using Alma M. Hawkins creation method, which is carried out in three stages: exploration, improvisation, and formation. The works discussed are two two-dimensional artworks entitled “Mati Sajroning Urip” and “Ajeg”. The method of analysis used to discuss the sample works is Feldman s method of analysis, which consists of description, formal analysis, and interpretation. The result of this research shows the presence of dragon objects in the artworks taken from the story of Dewa Ruci, which represent humans with their duality: the nurturing side and the destructive side that are necessary to achieve true perfection. The use of red represents lust, white represents emptiness (suwung), and gold represents the peak of spiritual experience.